Extracellular vesicular miRNA expression is not a proxy for skeletal muscle miRNA expression in males and females following acute, moderate intensity exercise. Issue 16 (18th August 2020) - Silver, Jessica L.; Alexander, Sarah E.; Dillon, Hayley T.; Lamon, Séverine; Wadley, Glenn D.
Abstract: Skeletal muscle and extracellular vesicle (EV) miRNA expression increases following acute endurance exercise. However, research to date has only been performed in males. The aim of this study was to describe the expression levels of a subset of miRNAs in EVs following acute exercise and compare it to skeletal muscle miRNA expression. Twelve males (age 22.9 ± 2.6 years, mean ±  SD ) and eight females (age 23.0 ± 3.4 years) cycled for 60 min at 70% VO2 peak. Muscle biopsies and blood samples were collected at rest, immediately after and 3 hr after exercise. Acute exercise did not significantly alter the expression of miR‐1, miR‐16, miR‐23b and miR‐133a/b in EVs in males and females combined. There were no correlations between EV and skeletal muscle miRNA expression in any of the measured species at any time point. Exploratory analysis revealed differential miRNA responses to exercise between males and females. In males, a weak negative correlation was observed between skeletal muscle and EV miR‐16 expression immediately following exercise; however, the physiological relevance of this correlation is unknown. Additionally, when compared with values at rest, male skeletal muscle miR‐16 expression significantly increased immediately following exercise, whereas miR‐133a expression significantly decreased 3 hr post exercise. Our findings suggest that miRNAs isolated from EVs are not a proxy for skeletal muscle miRNA content. Our exploratory data is the first known evidence of sex‐specific differences in the miRNA response to an acute bout of endurance exercise, particularly for miRNA species implicated in mitochondrial metabolism and angiogenesis. Abstract : Male skeletal muscle ( n  = 12) miRNA expression (miR‐16, ‐133a, ‐1, ‐23b and ‐133b; A‐E, respectively) in response to 60 min of cycling at 70% VO2peak. A one‐way, repeated measures ANOVA was used to identify significant differences in miRNA expression over time. Individual data points shown for each participant along with mean ±  SD . * p  < .05; ** p  < .01.